Highly resolved and refreshable X-ray imaging from Tb3+ doped aluminosilicate oxyfluoride glass scintillators. Issue 6 (31st January 2023) - Chen, SunYueZi; Li, LianJie; Chen, JunYu; Xu, ShuJun; Huang, WenJun; Wen, ZhuoXing; Jiang, TingMing; Guo, Hai
Abstract : A glass scintillator with high spatial resolution of 20 lp mm −1 and refreshable X-ray imaging is designed. The practical tests also reveal the great potential for applications in X-ray imaging. Abstract : Radiation detection is of current interest for diverse applications, such as biomedical diagnostics, computerised tomography scanning and safety detection. High-quality radiation imaging for targeted objects with irregular shapes requires use of scintillators with high resolution, large scale and moderate radiation tolerance. Here, a series of Tb 3+ doped aluminosilicate oxyfluoride glass samples are designed. Strong photoluminescence excited by ultra-violet light and radioluminescence excited by X-ray were obtained. The optimal specimen presents a highly integrated X-ray excited luminescent intensity (163% of that of a commercial Bi4 Ge3 O12 scintillator). The specimen also exhibits highly resolved X-ray imaging with an extraordinary spatial resolution (20 lp mm −1 ), which surpasses that of many halide scintillators, and might be a record resolution for a glass scintillator. The soft glass network furnishes the possibility for refreshable X-ray imaging. Those results provide a valid platform for glass scintillators for the practical utilisation in large areas and high-resolution imaging.